Academics well-being as a pillar of institutional autonomy: A study on work-life balance in higher education amidst and post Covid-19 - Shange, M.; Nyide, C. (South African Journal of Higher Education, 2025)
In higher education, intricate relationships among academic freedom, academic welfare, institutional autonomy, and public accountability have become increasingly evident. This research investigates the critical issue of balancing work and home lives for academics and its significant ramifications. This research aimed to evaluate the influence of work life balance on academics productivity at a specific university in South Africa. Three sophisticated quantitative approaches, the JD-R Model, structural equation modelling (SEM), and Analysis of Moment Structures (AMOS) 27 statistical software, were applied in the study of 175 full-time academics. The results of this research indicated a substantial negative connection among academics performance and work life imbalance (β = -0.232†, p < 0.100). This is an example of how difficult it is to be an academic and have a life. It is evident that productivity and meaningful contributions to an institution will increase when academics are able to successfully manage their personal and professional lives. However, institutional autonomy has an impact on administrative decisions and measures, which in turn affect the work environment, resources at disposal, job security, and overall welfare of academics.